Genome-wide association study for four measures of epigenetic age acceleration and two epigenetic surrogate markers using DNA methylation data from Taiwan Biobank. Issue 11 (28th December 2021) - Lin, Wan-Yu
Abstract: To highlight the genetic architecture for epigenetic aging, McCartney et al. recently identified 137 significant single-nucleotide polymorphisms based on genome-wide association study (GWAS) meta-analyses of four epigenetic clocks and two epigenetic surrogate markers. However, none Asian ancestry studies have been included in this or previous meta-analyses. I performed a GWAS on blood DNA methylation (DNAm) levels of 2309 Taiwan Biobank (TWB) participants. Owing to the fact that the sample size of an individual GWAS of DNAm data is still not large, I adopted the 'prioritized subset analysis' (PSA) method to boost the power of a GWAS. The four epigenetic clocks and the two epigenetic surrogate markers were investigated, respectively. I replicated 21 out of the 137 aging-associated genetic loci by applying the PSA method to the TWB DNAm data. Moreover, I identified five novel loci, including rs117530284 that was associated with the 'epigenetic age acceleration' (EAA) according to Lu et al. 's GrimAge (called 'GrimEAA'). Considering 16 covariates (sex, BMI, smoking status, drinking status, regular exercise, educational attainment and the first 10 ancestry principal components), each 'A' allele of rs117530284 in the IBA57 gene was found to be associated with a 1.5943-year GrimEAA (95% confidence interval = [1.0748, 2.1138]). IBA57 is a protein coding gene and is associated with multiple mitochondrial dysfunctions syndromes. A decline in mitochondrial activity and quality is associated with aging and many age-related diseases. This is one of the first DNAm GWAS for individuals of Asian ancestry.